Assessing electronic properties of desymmetrized heterocyclic patterns: towards tuning small molecules for photovoltaic applications. (2020) - González-Antonio, Oscar; Yépez, Rebeca; Vázquez-Alvarado, María Magdalena; Flores-Pérez, Blas; Farfán, Norberto; Amador-Bedolla, Carlos; Romero-Ávila, Margarita; Santillan, Rosa
Abstract: A series of highly attainable desymmetrized heterocyclic compounds with Donor-Acceptor-Donor-Acceptor-X (D-A-D-X) architectures were synthesized. The structures, where X corresponds to a heteroaromatic portion (pyridine, ferrocene, thiadiazolopyridine), were designed through computational analysis. Molecular geometries for all compounds were studied and parameters of charge transfer were computed in order to analyse the behaviour in each architecture. Spectroscopic properties (maximum absorption wavelengths, extinction coefficients and HOMO-LUMO gaps) were predicted and measured experimentally. UV-Vis absorption profiles and values of HOMO-LUMO optical gaps (in the vicinity of 2.0 eV), together with the computational results, are properties that position the obtained systems, as potential candidates for developing efficient photovoltaic materials based on synthetically accessible small organic molecules.